HUBUNGAN LINGKUNGAN TEMPAT TINGGAL DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR SISWA SMK JURUSAN PERIKANAN - Sambara, Piether M; Sape, Herwandi (Jurnal Riset Guru Indonesia, 2023)
This research is an experimental research conducted at SMK Negeri 1 Maros. This study aims to determine the relationship between living environment and learning motivation with student achievement. The population in this study were all grade XI students of SMK Negeri 1 Maros in the fisheries department in the 2023/2024 academic year. Furthermore, the sample in this study was 100% of the population, namely 72 students. The instruments used to collect data in this study were a questionnaire of student learning motivation factors and a questionnaire of living environment factors. Meanwhile, to obtain data on student learning achievement, researchers took student test scores for the 2023/2024 school year. In this study, two statistical analysis techniques were used, namely descriptive statistical analysis and inferential analysis. Based on the results of descriptive and inferential analysis, it was found that: 1) there is a significant positive relationship between neighborhood factors and student learning achievement. The amount of variation that occurs in the value of the student learning achievement variable that can be explained by the score of the living environment factor is 26.35%. The relationship is expressed in the regression equation = 29.122 + 0.5765X1. This shows that in general the factors of the student's living environment make a positive contribution in an effort to improve student learning achievement, 2) there is a significant positive relationship between student learning motivation factors and student learning achievement. The amount of variation that occurs in the value of the student learning achievement variable that can be explained by the score of the student learning motivation factor is 95.58%. The relationship is expressed in the regression equation = 2.6568 + 1.0015X2. This shows that in general the student learning motivation factor makes a positive contribution in an effort to improve student learning achievement, and 3) there is a significant positive relationship between environmental factors and student learning motivation factors together with student learning achievement. The amount of variation that occurs in the value of the student learning achievement variable that can be explained by the score of the living environment factor and the student learning motivation factor together is 95.72%. The relationship is expressed in the regression equation = 1.2276 + 0.0475X1 + 0.9802X2. This shows that in general, the living environment factor and the student learning motivation factor make a positive contribution in an effort to improve student learning achievement.